2014
DOI: 10.1177/0284185113514967
|View full text |Cite
|
Sign up to set email alerts
|

Histogram analysis of apparent diffusion coefficient map of diffusion-weighted MRI in endometrial cancer: a preliminary correlation study with histological grade

Abstract: Histogram analysis of ADC maps based on entire tumor volume can be useful for predicting the histological grade of endometrial cancer. The 90th and 95th percentiles of ADC were the most promising parameters for differentiating high from low grade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
87
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 25 publications
6
87
1
Order By: Relevance
“…By using this approach, minimum, 10th, 25th, 50th, 75th, and 90th percentile ADCs were significantly lower in grade 3 tumors than in grades 1 and 2 tumors (35). In a study of 33 patients, Woo et al (47) showed significant differences in ADCs between grades by using histographic analysis and total tumor volume. In their study, the 90th and 95th percentiles of ADCs were the most promising parameters for differentiating highfrom low-grade tumors (47).…”
Section: Discussionmentioning
confidence: 98%
“…By using this approach, minimum, 10th, 25th, 50th, 75th, and 90th percentile ADCs were significantly lower in grade 3 tumors than in grades 1 and 2 tumors (35). In a study of 33 patients, Woo et al (47) showed significant differences in ADCs between grades by using histographic analysis and total tumor volume. In their study, the 90th and 95th percentiles of ADCs were the most promising parameters for differentiating highfrom low-grade tumors (47).…”
Section: Discussionmentioning
confidence: 98%
“…The histogram approach has been increasingly used for heterogeneous tissues, allowing interpretation of the complex nature and features seen in tumors 17. Previous studies in adults have utilized histogram analysis of ADC and cerebral blood volume (CBV), which has been applied to a variety of scenarios including differentiation of true tumor progression from pseudoprogression,28, 29 response to chemotherapy,30 and grading of tumors 31, 32, 33. Most previous pediatric studies have reported mean or median ADC values based on a single section or slice, which does not address the heterogeneity seen in many abdominal tumors 7, 8…”
Section: Discussionmentioning
confidence: 99%
“…However, the commonly used average ADC measurement ignores the heterogeneity of the tumors, which is an important characteristic of both benign and malignant tumors. Due to its ability to analyze lesions pixel by pixel, histogram analysis was regarded as an effective method to deal with this problem (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). In a recent study, Donati et al (20) found that the 10th percentile ADC value correlated with Gleason score, suggesting the 10th percentile ADC value could help differentiate low-grade from intermediate or high-grade prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…ROI approach that places ROI on a representative section of the tumor, which is subjective and prone to sampling bias (14,17). A whole-tumor ROI approach that encompasses the entire tumor, would provide more information about the heterogeneity of the tumor, thus it can potentially eliminate sampling bias during data processing (13,16,17,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation